Context-dependent effect of serpulid reefs on the variability of soft-bottom macrobenthic assemblages in three Mediterranean lagoons (Sardinia, Italy). (5th November 2021) - Brundu, G.; Magni, P.
Abstract: In the present study, we investigated and compared the spatial variation in soft-bottom macrozoobenthic assemblages and associated sediments in three coastal lagoons colonized by mixed serpulid reefs of Ficopomatus enigmaticus and Hydroides dianthus, differing in extension, density, and confinement condition. We hypothesized that the effect of serpulid reefs on the benthic assemblages varies among lagoons, and that the pattern of spatial variation in the benthic assemblages at two distances (<1 m and 10's m apart) from serpulid reefs also differs among lagoons. The PERMANOVA revealed significant differences in the benthic assemblages of the three lagoons. In particular, the most marine and species-rich lagoon of Corru S'Ittiri, and the Santa Giusta lagoon, were dominated by bivalves and polychaetes, while the most confined, brackish San Giovanni lagoon, which had the least number of species, was dominated by highly abundant crustaceans, consistent with the presence of macroalgal cover. Moreover, we found significant differences in the variation in the benthic assemblages at the <1 m and 10's m locations in Corru S'Ittiri and Santa Giusta, but not in San Giovanni. These differences paralleled differences in sediment composition which were reciprocally influenced by serpulid reefs. In particular, hard-bottom species, e.g. the bivalve Mytilaster minimus, dominated at locations rich in carbonates and calcareous tube fragments, whilst soft-bottom species, such as Naineris laevigata, Abra segmentum and Alitta succinea, occurred more abundantly at some organic-enriched, muddy locations near the reefs. This work represents an original approach to investigate the effect of serpulid reefs as a hotspot of biodiversity in Mediterranean lagoons. The three studied lagoons, used to encompass the high variability of these ecosystems, demonstrate for the first time that the effect of serpulid reefs on soft-bottom benthic assemblages and their spatial variation within a lagoon varies depending on local interlinked environmental conditions, including reefs characteristics, confinement levels, sediment composition, and marine influence. Highlights: Serpulid reefs' effect on soft-bottom macrozoobenthic assemblages assessed in three Sardinian lagoons Significant variation in benthic assemblages among lagoons and at two distances from serpulid reefs found Hard-bottom species, e.g. Mytilaster minimus, dominated at carbonate-rich locations Soft-bottom species, e.g. Naineris laevigata, Abra segmentum and Alitta succinea, abundant at organic-rich muddy locations Reef and sediment characteristics, degree of confinement and salinity influenced the spatial variation in benthic assemblages